Պոլսահայերի օգնությունը Հայաստանի առաջին Հանրապետությանը և Խորհրդային Հայաստանին (1919–1922 թթ.) - Մալհասյան, Սիլվարթ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Константинопольские армяне с первых же дней приветствовали провозглашение Первой Республики Армении в мае 1918 года, но не могли открыто выражать свои чувства. После официального признания Армянской Республики Парижской мирной конференцией 19 января 1920 года они гораздо свободнее проявляли свое воодушевление и начали участвовать в оказании помощи Родине. Помощь Армении организовывали религиозные лидеры трех церквей во главе Армянского Патриархата Турции. Проводились различные культурные мероприятия. Откликаясь на призывы Республики Армения, армяне Константинополя были привержены поддержке правовых, экономических, военных, конституционных, профессиональных и культурных потребностей Родины. Вклад армян Константинополя был важен в организации облигаций госзайма Первой Республики Армения. From the very first days, the Armenians of Constantinople welcomed the proclamation of the First Republic of Armenia in May 1918, but could not openly express their feelings. After the official recognition of the Armenian Republic by the Paris Peace Conference on January 19, 1920, they showed their enthusiasm much more freely and began to participate in helping their Motherland. The assistance to Armenia was organized by the religious leaders of three churches headed by the Armenian Patriarchate of Turkey. Various cultural events were held. Responding to the appeals of the Republic of Armenia, the Armenians of Constantinople were committed to supporting the legal, economic, military, constitutional, professional and cultural needs of the Homeland. The contribution of the Armenians of Constantinople was important in the organization of the bonds of the state loan of the First Republic of Armenia.
Keywords: Պատմություն